2010
DOI: 10.1021/jf100513j
|View full text |Cite
|
Sign up to set email alerts
|

Di-d-fructose Dianhydride-Enriched Caramels: Effect on Colon Microbiota, Inflammation, and Tissue Damage in Trinitrobenzenesulfonic Acid-Induced Colitic Rats

Abstract: In the present study we describe the preparation and chemical characterization of a caramel with a high (70%) content of difructose dianhydrides (DFAs) and glycosylated derivatives (DFAs). This product was obtained by thermal activation (90 degrees C) of highly concentrated (90% w/v) aqueous D-fructose solutions using the sulfonic acid ion-exchange resin Lewatit S2328 as caramelization catalyst. DFAs represent a unique family of cyclic fructans with prebiotic properties already present in low proportions (<15%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 38 publications
0
29
0
Order By: Relevance
“…Arribas et al (2010) recently showed that the administration of a DFA-enriched caramel obtained from fructose (containing 70% of an isomeric mixture of 13 DFAs and glycosyl-DFAs, identical to FC in this work) to colitic rats promoted a more favourable intestinal microbiota, increasing lactobacilli and bifidobacteria log 10 number of copies, as well as inducing increased concentrations of SCFA in the luminal colonic contents. Previous results on the prebiotic potential of a caramel obtained by pyrolysis of sucrose in the presence of citric acid (Manley-Harris and Richards, 1997) containing~34% of DFAs and 43% of monosaccharides indicated that DFAs and their glycosylated derivatives might represent promising candidates as prebiotic agents (Orban et al, 1997).…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Arribas et al (2010) recently showed that the administration of a DFA-enriched caramel obtained from fructose (containing 70% of an isomeric mixture of 13 DFAs and glycosyl-DFAs, identical to FC in this work) to colitic rats promoted a more favourable intestinal microbiota, increasing lactobacilli and bifidobacteria log 10 number of copies, as well as inducing increased concentrations of SCFA in the luminal colonic contents. Previous results on the prebiotic potential of a caramel obtained by pyrolysis of sucrose in the presence of citric acid (Manley-Harris and Richards, 1997) containing~34% of DFAs and 43% of monosaccharides indicated that DFAs and their glycosylated derivatives might represent promising candidates as prebiotic agents (Orban et al, 1997).…”
Section: Discussionmentioning
confidence: 54%
“…Recently, caramelization technologies, based on the use of heterogeneous acid catalysts, have been developed that allow producing DFA-enriched products (up to 70-80% DFAs and glycosyl-DFAs) from fructose or fructose-containing mixtures of food-grade carbohydrates . Initial results in rats fed with a fructose-derived DFA-enriched caramel were consistent with a prebiotic behaviour associated with the preservation of a healthy microbiota equilibrium (Arribas et al 2010). Investigating the nutritional effects of these new caramels with high DFA content in farm animals was then very appealing.…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…Full-thickness sections of 5 mm were obtained at different levels and stained with hematoxylin and eosin. The histological damage was evaluated by a pathologist observer, who was blinded to the experimental groups, according to the criteria previously described by Arribas et al (2010).…”
Section: Evaluation Of Colonic Damagementioning
confidence: 99%
“…Equivalent colonic segments were also obtained from the non-colitic group: 5-μm paraffin sections were cut at different levels and stained with hematoxylin and eosin. The histologic damage was evaluated by two pathologists blinded for the study following the criteria reported by Arribas et al, 38 and images were taken by standard light microscopy using an Olympus CX41 microscope (Olympus Iberia, S.A.U., Barcelona, Spain). The colon was subsequently minced, aliquoted, and kept frozen at −80°C until biochemical determinations and RNA extraction were performed.…”
Section: In Vivo Evaluation Of the Bioactivity Of Functionalized Sfnsmentioning
confidence: 99%